Fishery management and extended maritime jurisdiction The Philipine tuna fishery situation. - Aprieto, Virginia L. (Honolulu, Hawaii East-West Center, 1981)
Research report / East-West Environment and Policy Institute ; no. 4
Keywords: Economic zones (Maritime law)--Philippines.; Fishery policy--Philippines.; Tuna fisheries--Philippines.